2013
DOI: 10.7213/archivesoforalresearch.09.002.ao01
|View full text |Cite
|
Sign up to set email alerts
|

Reasons and pattern of tooth mortality as perceived by dental professionals in Udaipur City, Rajasthan, India

Abstract: Objectives: The aim of the present study was to assess the reasons for tooth mortality as perceived by the dentists for the patients attending the dental clinics and hospitals in Udaipur city. Material and methods: A closed-ended questionnaire survey was conducted among 211 dental practitioners of Udaipur city. The reasons for extraction of permanent and deciduous teeth among patients who had attended during the study period were categorized and the dentists were requested to record the age and sex of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…Studies have found no significant difference between missing FPM on the right or left side of the dental arches. 17 , 18 Similar to previous studies, this study found no statistically significant difference between the number of missing FPM on the right or left side of the arches ( p = 0.392). However, lower left FPM was found to be missing more frequently than the FPM in other quadrants, which corroborates with the findings of other authors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies have found no significant difference between missing FPM on the right or left side of the dental arches. 17 , 18 Similar to previous studies, this study found no statistically significant difference between the number of missing FPM on the right or left side of the arches ( p = 0.392). However, lower left FPM was found to be missing more frequently than the FPM in other quadrants, which corroborates with the findings of other authors.…”
Section: Discussionsupporting
confidence: 89%
“… 15 , 16 Halicioglu et al 10 in a study on 13–20-year-old Turkish group found that lower FPMs were more frequently missing (66%) than the upper FPMs (34%) and the difference was statistically significant. Bhat et al 17 determined the prevalence of missing mandibular and maxillary FPMs to be 21% and 10%, respectively. However, Demirbuga et al 18 had reported lower rates of missing permanent first molar teeth in the mandible (2.77%) and maxilla (1.17%) compared with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, chewing and cleaning habits and the residence time of food in the mouth may play important roles in ra tes of extraction on the left or right sides of the jaws. In contrast, Bhat et al 21 found no significant difference between ra tes of extraction on the left and right sides of the oral cavity. Demirbuga et al 18 reported that right side missing teeth numbered 302 (1.91%) and left side missing teeth amount to 321 (2.03%), and they did not find statistical differences between the right and left sides of jaws.…”
Section: Discussionmentioning
confidence: 87%
“…Barbato and Peres 20 claimed that this finding could be explained by the fact that females use more dental services due to their deeper health or aesthetic concerns, which may lead to overtreatment. On the contrary, Bhat et al 21 reported that the percentages of extracted teeth in males were 53.1% and in fe males were 46.9%. Jafarian and Etebarian 7 assessed that males comprised 48.7% of patients, but they had more extracted teeth (56.1%) than females (43.9%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation